2020
DOI: 10.1021/acs.energyfuels.0c03081
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Shear Viscosity of Carbonated Aqueous Amine Solutions and Their Blends by Using an Artificial Neural Network Model

Abstract: In the present work, a neural network (NN) model based on quantitative structure−viscosity relationship was implemented for predicting the shear viscosity of CO 2 -loaded and CO 2 -free aqueous amine solutions and their blends. A total of 1682 amine + CO 2 + water viscosity data sets for primary, secondary, and tertiary amines and 220 data points for further accuracy examinations were used. Molecular mechanic methods with CHARMM + CFF force fields were utilized in order to optimize, simulate, and extract the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Talasila et al [ 18 ] proposed a tiered teaching method based on music pedagogy theory in order to improve the teaching efficiency and overall stability of higher education music teaching classroom by studying and analysing different students in various aspects. Aminian and Zarenezhad [ 19 ] validated it through teaching practice and the final results showed that the teaching method was effective in improving. Forrester [ 4 ] proposed a new teaching method for grouped music teaching in colleges and universities based on hyperchaotic mapping, which uses the deformed chaotic sequences to positionally displace the original college music teaching method to achieve an optimal teaching plan for the college music teaching classroom teaching process.…”
Section: Related Workmentioning
confidence: 99%
“…Talasila et al [ 18 ] proposed a tiered teaching method based on music pedagogy theory in order to improve the teaching efficiency and overall stability of higher education music teaching classroom by studying and analysing different students in various aspects. Aminian and Zarenezhad [ 19 ] validated it through teaching practice and the final results showed that the teaching method was effective in improving. Forrester [ 4 ] proposed a new teaching method for grouped music teaching in colleges and universities based on hyperchaotic mapping, which uses the deformed chaotic sequences to positionally displace the original college music teaching method to achieve an optimal teaching plan for the college music teaching classroom teaching process.…”
Section: Related Workmentioning
confidence: 99%